Important Components Of International Students adaptation For Studying At Higher Educational Institutions - Borysenko, Tetyana; Shakhova, Olena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article highlights results of the most topical problems study in international students, which complicate their social and psychological adaptation. Typical ways of solving these problems, by students are revealed. Negative social phenomena which are common among students are determined. The level of need among international students in psychological support and the degree of its awareness was studied, the most important and interesting forms and methods of work in carrying out psychological support for them are determined.